ANALISIS PERKEMBANGAN EKONOMI ISLAM DI ASIA TENGGARA (Sebuah Kajian Historis) - Akmal, Haerul; Ghozali, Mohammad (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2017)
Abstract : The development of Islamic Economy in several Asian countries through many processes, among them is the establishment of a Law or a Government Regulation. The development of Islamic economics in several Asian countries such as Indonesia, Malaysia, Singapore, Thailand and Brunei Darussalam, can be seen from the growth of Banking in each of these countries. The method used in this writing is the Writing Method Library Reseach. This study yielded some important points, that the development of Islamic economics in the countries that become the object of research, originated from the seriousness of the Muslims to establish sharia-based banking, because in the minds of minority Muslims, that they have the right to consume halal banking products and in accordance with their religious teachings. The aspirations of these Muslims are not only heard by the local government, but the government's attention is on their aspirations. In the end, as a proof of the concern, a regulation was issued concerning the opening of banking with profit sharing or non-interest system.Keywords : Islamic Economy,Sharia Banking